PENINGKATAN KETERAMPILAN MENULIS LAPORAN SEDERHANA MELALUI MODEL PEMBELAJARAN TWO STAY TWO STRAY PADA TEMA 4 â€œHIDUP BERSIH DAN SEHATâ€ - Mega Dewi Harjayanti; C. Indah Nartani (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2018)
This research was aimed at describing the improvement of skill in writing simple report using two stay two stray learning model on four theme Â â€œLiving Clean and Healthyâ€ for students of grade II at SD Negeri Golo Yogyakarta school year 2017/2018. The type of this research was Classroom Action Research (CAR) which was conducted in twoÂ cycles. The result of this research showed that by using two stay two stray learning model could improve the skill in writing simple report for students in class IIB at SD Negeri Golo Yogyakarta. The students mean score obtained in the pre-test was 58,96 and increased into 68,33 in the post-test of Cycle I and become 76,04 in the post-test of Cycle II. Based on the result of the research, it could be concluded that the use of two stay two stray learning model could improve second grade students skill in writing simple report at SD Negeri Golo Yogyakarta.